Efficiency change in Pakistan commercial banking sector : a pre and post digital-restructuring analysis / Sadaf Mustafa and Bilal Mehmood - Mehmood, Bilal (Faculty of Business and Management, 2015)
In this study we examine the technical efficiency of commercial banking sector of Pakistan. In recent past Pakistan’s commercial banking is making substantial investment and up-gradation in information and communication technology (ICT) in order to keep pace with global banking industry. Due to financial linearization the entry of the foreign banks with advance technology in the commercial banking sector has been increased that inclines other banks to adopt the new technology in order to earn more of market share. To justify the huge investments in computers and related technologies many question arises about the efficiency & productivity growth of the banks due to ICT. Accordingly, this study analyzes the efficiency of a sample of 11 commercial banks for the period 1998 to 2012. Using data envelopment analysis (DEA) we measure the Malmquist productivity index (MPI) to measure total factor productivity (TFP). In this study the time period (1998-2012) has been decomposed into pre-digital reforms (1998- 2005) & post-digital reforms (2006-2012) period, in order to compare the efficiency change after the adaptation of IT by commercial banking sector. The variables are selected under intermediation approach. The results show that technical efficiency has been significantly increased in post-digital reform era and as a result TFP has also been boosted. The results show that MCB has consistently scored the highest efficiency & Malmquist TFP scores.